Family farming: vulnerabilities, challenges and confrontations - Joao Manoel da Silva; Jakes Halan de Queiroz Costa (Universidade Estadual de Alagoas, 2023)
Currently, there is an enormous need and search for healthy food, as well as means of agricultural production that are less harmful to biodiversity. Family farming is a form of agricultural production based on family reproduction and is responsible for the production of most of the food consumed by the Brazilian population, since it is not aimed at the production of commodities. In this sense, these social analytical categories also aim at a production with more sustainable and fair guidelines. In this sense, the objective of this study was to discuss the vulnerabilities and problems faced by family farming. Through this immersion it is possible to understand that there are still needs to be faced, especially to the detriment of public policies and social education.